To make the equation have no solution, we need to create a contradiction. One way to do this is to make the coefficients on the x terms unequal.
To achieve this, we can multiply the second equation by a non-zero constant. Let's choose -5:
5x + 12 = -5x - 45
Now we have:
5x + 12 = -5x - 45
Adding 5x to both sides:
10x + 12 = -45
Subtracting 12 from both sides:
10x = -57
Dividing by 10:
x = -57/10
So the solution is a single number, which means there is no solution that satisfies both equations simultaneously.
Complete the equation so that it has no solution.(1 point)
5x+12=
x+9
4 answers
Complete the equation so that it has no solution.(1 point)
5x+12= x+9
5x+12= x+9
Solve for x to determine if the equation has one, none, or infinite solutions.
6(2x+4)−24=12x
(1 point)
Responses
The equation has one solution: x=−20.
The equation has one solution: x equals negative 20 .
The equation has no solution.
The equation has no solution.
The equation has infinite solutions.
The equation has infinite solutions.
The equation has one solution: x=0.
The equation has one solution: x equals 0 .
6(2x+4)−24=12x
(1 point)
Responses
The equation has one solution: x=−20.
The equation has one solution: x equals negative 20 .
The equation has no solution.
The equation has no solution.
The equation has infinite solutions.
The equation has infinite solutions.
The equation has one solution: x=0.
The equation has one solution: x equals 0 .
Which of the following is an example of an equation with no solution?(1 point)
Responses
3x+4=3x+3
3 x plus 4 equals 3 x plus 3
4x+3=3x+3
4 x plus 3 equals 3 x plus 3
3x+4=3x+4
3 x plus 4 equals 3 x plus 4
3x+4=4x+3
3 x plus 4 equals 4 x plus 3
Responses
3x+4=3x+3
3 x plus 4 equals 3 x plus 3
4x+3=3x+3
4 x plus 3 equals 3 x plus 3
3x+4=3x+4
3 x plus 4 equals 3 x plus 4
3x+4=4x+3
3 x plus 4 equals 4 x plus 3